SAMPUL ALBUM MUSIK SEBAGAI MEDIA BEREKSPRESI (ANALISIS SEMIOTIKA CHARLES SANDERS PEIRCE TERHADAP SAMPUL ALBUM "SWIMMING" KARYA MAC MILLER) - Shabrina Putri Nisakara (2023)
This study relies on the background of how music is not only seen as entertainment but also as a medium for expression. Inside a musical work, song is not the only thing considered as an art work, there is usually another art work in the form of visual image called album cover. Commonly, album cover is known only as the album packaging or complementarity. However, album cover can also be used as a medium for the musician to communicate with their audience visually. This study specifically specifies the music album cover of "Swimming" by rapper Mac Miller. Miller is known as a musician who talks and expresses his feelings and thoughts through the music he creates. The aim of this study is to know how Miller doesn't only use lyrics in his songs to express verbally but also to express visually through the album cover of his music albums using signs and symbols in the form of images. This study is done using Charles Sanders Peirce's semiotic analysis. The method used in this study is descriptive qualitative with a semiotic approach and interpretative behavior. This study uses documentation study as the data collection technique with primary and secondary data sources. This study is guided using the data analysis technique of Charles Sanders Peirce's triadic model that consist of three elements which are representamen/sign, object and interpretant. The result of this study shows that each element inside the album cover of "Swimming" by Mac Miller exhibits a sense of awareness. This awareness refers to the fact that Miller understands where he is in his live at that moment of place and time. Lastly, it can be concluded that album cover can be used as a medium to visually communicate expressions.